Report about mollusc diseaes - Berthe, Franck (CIHEAM-IAMZ, 2004)
Of the 75 laboratories contacted through the survey, 54 answered, 14 of which are partially or totally devoted to mollusc diseases. In fact, only 4 laboratories are devoted full-time to this work. Of the 14 laboratories that declared to work on the diagnosis of mollusc diseases, 12 stated that they worked with mussels, 12 with oysters, 9 with clams and 8 with other mollusc species. This is coherent with available production information. According to production data in 2001 (FAO source), the main mollusc species in the region are the blue mussel, Mytilus edulis (297,485 tonnes), the Mediterranean mussel, Mytilus galloprovincialis (131,014 tonnes), the Pacific cupped oyster, Crassostrea gigas (127,323 tonnes, an important part of which is produced on the Atlantic coast of France), the Japanese carpet shell clam, Tapes spp. (56,778 tonnes), and the European flat oyster, Ostrea edulis (5991 tonnes). France (oysters and mussels), Spain (principally mussels and to a lesser extent clams) and Italy (mussels and clams) are the three main producing countries in the region. Distribution per country is as follows: 3 laboratories in Spain, 2 in France, 2 in Greece, 1 in Italy, 1 in Portugal, 1 in Croatia, 1 in Romania, 1 in Israel, 1 in Morocco and 1 in Tunisia. These laboratories include 1 OIE Reference Laboratory and Community Reference Laboratory for mollusc diseases, and 4 National Reference Laboratories (EU Directive 95/70/EC).